The Understanding of Shirah Nabawiyah Santri TPA Baitul Izzah Mosque, Kuta Blang, Bireuen Regency Through Storytelling Methods Assisted by Islamic Comics - Muthmainnah Muhammad (Genderang Asa: Journal of Primary Education, 2023)
Rasulullah SAW is the main example of the Islamic community. Planting his example should be done from an early age through Shirah Nabawiyah. In Shirah Nabawiyah there are many historical values ​​in the form of stories about past events both during the time of Rasulullah SAW and after he died. The length of the stories of the Prophet's life will be very difficult for students to understand if only by reading. Therefore we need a method that is most appropriate to tell it so that students can understand it deeply and efficiently. This method is a storytelling method with the help of Islamic comic media. This is the object of this research. The sample of this research is Santri TPA Baitul Izzah Mosque, Kec. Krueng Panjoe, Kab. Bireuen which amounted to 30 people. The results of this study indicate that students find it easier to understand Shirah Nabawiyah when conveyed through the application of the storytelling method with the help of Islamic comic media. It can be concluded that students' understanding can be identified by the emergence of several cognitive indicators where students are able to interpret, give examples, classify, explain, summarize, and conclude.